Ultra-fast prompt gamma detection in single proton counting regime for range monitoring in particle therapy. (16th December 2020) - Marcatili, S; Collot, J; Curtoni, S; Dauvergne, D; Hostachy, J-Y; Koumeir, C; Létang, J M; Livingstone, J; Métivier, V; Gallin-Martel, L; Gallin-Martel, M L; Muraz, J F; et al.
Abstract: In order to fully exploit the ballistic potential of particle therapy, we propose an online range monitoring concept based on time-of-flight (TOF)-resolved prompt gamma (PG) detection in a single proton counting regime. In a proof of principle experiment, different types of monolithic scintillating gamma detectors are read in time coincidence with a diamond-based beam hodoscope, in order to build TOF spectra of PG generated in a target presenting an air cavity of variable thickness. Since the measurement was carried out at low beam currents (< 1 proton/bunch) it was possible to reach excellent coincidence time resolutions, of the order of 100 ps ( σ ). Our goal is to detect possible deviations of the proton range with respect to treatment planning within a few intense irradiation spots at the beginning of the session and then carry on the treatment at standard beam currents. The measurements were limited to 10 mm proton range shift. A Monte Carlo simulation study reproducing the experiment has shown that a 3 mm shift can be detected at 2 σ by a single detector of ∼1.4 × 10 −3 absolute detection efficiency within a single irradiation spot (∼10 8 protons) and an optimised experimental set-up.